Vixen, Volume I. - Braddon, M. E. (Mary Elizabeth), 1835-1915 (Salt Lake City, UT : Project Gutenberg, 2008)
"Vixen, Volume I" by M. E. Braddon is a novel written in the late 19th century. The story revolves around Violet Tempest, affectionately nicknamed Vixen, a spirited young girl with a passion for life, horses, and adventure, as she interacts with her friends and family, including Roderick Vawdrey, her childhood companion. The narrative explores their complex relationships, set against the backdrop of the English countryside and societal expectations of the time. The opening of "Vixen" introduces us to Roderick Vawdrey, a young man who enjoys a late evening in the woods after a day of rabbit shooting. He is drawn to the home of the Tempests to bid farewell to Vixen, who is characterized by her lively spirit and self-willed nature. Their playful and teasing exchange reveals a deep bond between them, hinting at the evolving dynamics as they both mature. The chapter captures an idyllic moment in their lives, setting the stage for the challenges and changes to come as they navigate the tensions between friendship, duty, and the expectations imposed by their families and society. (This is an automatically generated summary.)
Release date is 2008-08-09
Produced by Daniel Fromont. HTML version by Al Haines.
Keywords: Psychological fiction; Domestic fiction; English fiction -- 19th century; Women -- England -- Fiction